Teaching or research? What affects the efficiency of universities - Erik Lehmann; Susanne Warning (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 2002)
We examine differences in the efficiency of UK universities in providing research and teaching. It appears that (i) universities are more efficient in providing teaching than research, (ii) the variation of efficiency is larger in research than in teaching, and (iii) the degree of (in)efficiency is affected by student characteristics like gender, age and their regional provenance and background but also past political regulation.
Keywords: A20; D24; I21; 330; educational economics; efficiency analysis; performance indicators